The Cyprus Quandry: Geopolitics of Potential Hydrocarbon Wealth - Mehmet, Özay; Yorucu, Vedat (Springer, 2020)
The island of Cyprus sits in the very centre of Eastern Mediterranean hydrocarbons. Historically, it has always been a strategic location eagerly sought by outside powers, but in the recent past its fate has been further complicated by the deep-rooted rivalries within the island’s main ethnic groups, Greek and Turkish Cypriots, and in the wider regional context, between Greece and Turkey. © 2020, Springer Nature Switzerland AG.
Keywords: Energy management; Energy resources; Eastern Mediterranean; Ethnic groups; Strategic locations; Turkishs; Hydrocarbons